2017
DOI: 10.1200/jco.2016.71.9815
|View full text |Cite
|
Sign up to set email alerts
|

De-Escalation Strategies in Human Epidermal Growth Factor Receptor 2 (HER2)–Positive Early Breast Cancer (BC): Final Analysis of the West German Study Group Adjuvant Dynamic Marker-Adjusted Personalized Therapy Trial Optimizing Risk Assessment and Therapy Response Prediction in Early BC HER2- and Hormone Receptor–Positive Phase II Randomized Trial—Efficacy, Safety, and Predictive Markers for 12 Weeks of Neoadjuvant Trastuzumab Emtansine With or Without Endocrine Therapy (ET) Versus Trastuzumab Plus ET

Abstract: Purpose Human epidermal growth factor receptor 2 (HER2)-positive/hormone receptor (HR)-positive breast cancer is a distinct subgroup associated with lower chemotherapy sensitivity and slightly better outcome than HER2-positive/HR-negative disease. Little is known about the efficacy of the combination of endocrine therapy (ET) with trastuzumab or with the potent antibody-cytotoxic, anti-HER2 compound trastuzumab emtansine (T-DM1) with or without ET for this subgroup. The West German Study Group trial, ADAPT (Ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
99
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 123 publications
(101 citation statements)
references
References 18 publications
2
99
0
Order By: Relevance
“…Results from 2 randomized studies in the neoadjuvant setting already have been reported (Table ), including the phase 3 KRISTINE trial . Although these data indicate that T‐DM1 may not be as effective as chemotherapy plus trastuzumab and pertuzumab for high‐risk patients, it is associated with less toxicity . Two phase 3 trials are ongoing to assess its potential use in the adjuvant setting: the KATHERINE trial (clinicaltrials.gov identifier NCT01772472), which is comparing 1 year of T‐DM1 versus trastuzumab in patients who have residual disease after neoadjuvant therapy; and the KAITLIN trial (clinicaltrials.gov identifier NCT01966471), which is evaluating the combination of T‐DM1 and pertuzumab versus trastuzumab, pertuzumab, and a taxane after anthracyclines in both arms.…”
Section: Trastuzumab a Landmark In The Treatment Of Her2‐positive DImentioning
confidence: 99%
See 1 more Smart Citation
“…Results from 2 randomized studies in the neoadjuvant setting already have been reported (Table ), including the phase 3 KRISTINE trial . Although these data indicate that T‐DM1 may not be as effective as chemotherapy plus trastuzumab and pertuzumab for high‐risk patients, it is associated with less toxicity . Two phase 3 trials are ongoing to assess its potential use in the adjuvant setting: the KATHERINE trial (clinicaltrials.gov identifier NCT01772472), which is comparing 1 year of T‐DM1 versus trastuzumab in patients who have residual disease after neoadjuvant therapy; and the KAITLIN trial (clinicaltrials.gov identifier NCT01966471), which is evaluating the combination of T‐DM1 and pertuzumab versus trastuzumab, pertuzumab, and a taxane after anthracyclines in both arms.…”
Section: Trastuzumab a Landmark In The Treatment Of Her2‐positive DImentioning
confidence: 99%
“…48,49 T-DM1 is under active clinical investigation in early stage, HER2-positive breast cancer. Results from 2 randomized studies in the neoadjuvant setting already have been reported (Table 4), 50,51 including the phase 3 KRISTINE trial. 50 Although these data indicate that T-DM1 may not be as effective as chemotherapy plus trastuzumab and pertuzumab for high-risk patients, it is associated with less toxicity.…”
Section: Ado-trastuzumab Emtansinementioning
confidence: 99%
“…Although direct comparisons cannot be made with other studies due to differences in study design, region, and treatment regimens, the TRYPHAENA study reported a pCR rate (ypT0-isypN0) of 50.7% with the FEC+H+P×3 → T+H+P×3 regimen, 45.3% with the FEC×3 → T+H+P×3 regimen, and 51.9% with the TCH+P×6 regimen, the only comparable arm, compared with 57% in group A of this study [8]. The pCR rates in the ADAPT study were 41.0% for the T-DM1×4 regimen and 41.5% for the T-DM1+ET×4 regimen in patients with early HER2+ HR+ breast cancer [20]. However, in ADAPT, patients received 4 treatment cycles unlike 6 in our study.…”
Section: Discussionmentioning
confidence: 62%
“…In pre-menopausal women with ER+, ovarian suppression is often engaged using HT. In the ADAPT study, pCR rates were 41.5% and 15.1% in patients with HER2+ HR+ breast cancer receiving concomitant HT with 12-week T-DM1 and trastuzumab, respectively [20], suggesting improved efficacy of anti-HER2 therapy without any detrimental effects with concomitant HT. In the Neo-LaTH study [25], patients receiving anti-HER2 therapy (with/without HT) before chemotherapy for longer duration (18 versus 6 weeks) tended to show more tumor shrinkage.…”
Section: Discussionmentioning
confidence: 99%
“…Superiority was confirmed by a significant p-value and chemotherapy plus double HER2 targeting remains the treatment of choice in the neoadjuvant setting. A similar pCR rate obtained with T-DM1 alone in the West German study ADAPT in women with HER2 positive and HR positive breast cancer (41%) [23], strongly suggests that T-DM1 might be a potentially less toxic and less expensive option for selected patients who need neoadjuvant therapy. While newer drugs will be always welcome, not using active drugs that we already have in a more rationale, biomarker-guided way will remain a missed opportunity to optimize the therapeutic strategy in HER2 positive breast cancer.…”
Section: Expert Opinionmentioning
confidence: 56%